Leptin Levels are Associated with Subclinical Cardiac Dysfunction in Obese Adolescents - Imerbtham T; Thitiwuthikiat P; Jongjitwimol J; Nuamchit T; Yingchoncharoen T; Siriwittayawan D (Diabetes, Metabolic Syndrome and Obesity, 2020)
Thamonwan Imerbtham,1 Piyanuch Thitiwuthikiat,1 Jirapas Jongjitwimol,2 Teonchit Nuamchit,1 Teerapat Yingchoncharoen,3 Duangduan Siriwittayawan1 1Department of Cardio-Thoracic Technology, Faculty of Allied Health Sciences, Naresuan University, Phitsanulok, Thailand; 2Department of Medical Technology, Faculty of Allied Health Sciences, Naresuan University, Phitsanulok, Thailand; 3Department of Internal Medicine, Faculty of Medicine, Mahidol University, Bangkok, ThailandCorrespondence: Duangduan SiriwittayawanDepartment of Cardio-Thoracic Technology, Faculty of Allied Health Sciences, Naresuan University, Phitsanulok 65000, ThailandTel +66 55 966 417Fax +66 55 966 234Email duangduans@nu.ac.thPurpose: The purposes of this study were to use speckle tracking echocardiography to confirm the influence of obesity on cardiac functions and to assess their relationships with leptin and uric acid levels in obese adolescents.Methods: Eighty-one participants aged 16– 19 years were recruited and classified as either non-obese (n = 30) or obese (n = 51). Global longitudinal strain (GLS), leptin and uric acid levels for each group were assessed and compared. The data from obese participants were then compared based on their leptin levels and analyzed for correlation using regression analysis.Results: The obese group had significantly lower absolute GLS compared to the non-obese group (19.10 ± 0.30 versus 21.10 ± 0.30%, p < 0.001). In obese group, subclinical cardiac dysfunction was worse in the hyperleptinemic group than that of the normoleptinemic group (p = 0.03). Multivariate regression analysis showed that leptin and triglyceride levels were negatively associated with absolute GLS. Leptin could predict the absolute GLS with β = − 0.35 (p = 0.02).Conclusion: Subclinical left ventricular systolic dysfunction was found in obese adolescents, while GLS was worse in the hyperleptinemic subjects. Leptin, but not uric acid, levels were associated with a worsening of GLS.Keywords: leptin, global longitudinal strain, juvenile, speckle tracking echocardiography, uric acid